Theorizing Desire - Gorton, K. author. aut Link
X, 182 p.
Keywords: What is the nature of desire? This book gives an accessible introduction to the concept, and a coherent critique of the competing theories of desire within contemporary theory. Through analysis of representations of desire in television and film, it considers ways in which the concept is theorized and presented on screen.